DIGITAL IMAGE ANALYSIS WITH LONG EXPOSURE PHOTOGRAPHY TECHNIQUE FOR COLLISION PHENOMENA IN CAROM GAMES - Afrianto, Fahrizal
This study developed methods and devices that can carry out quantitative analysis of twodimensional collision that occur in carom games by using digital image analysis taken using long exposure technique. Long exposure is a technique of taking pictures on a camera that can record all traces of objects, especially objects that emit light and move at a certain time. In order to analyzed the motion, the traces of the motion which are continuous line must be converted into discrete traces. Camera devices that have been equipped with the long exposure feature must be placed in front of a rotating perforated disc. This disc functions as a chopper, which is the hole for the camera to capture the trajectory of the carom ball and turn it into discrete traces. The collision cases observed were collisions between carom pieces and carrom board walls and collisions between two carom pieces. The collision between the carom ball and the wall of the carom board was carried out with two sets, where the first set the chopper was arranged to have a rotating speed of ± 1540 rpm and the second set of chopper rotational speed was determined arbitrarily. From the experimental results it was found that in the two experimental sets, no kinetic energy conservation law was applied, because there was dissipated kinetic energy equal to 57.539% for the first set of experiments and 58.554% for the second set of experiments. Besides that, the momentum conservation law also does not apply, because there is a contact force during the collision process, which is equal to 0,374 N for the first set of experiments and 0,351 N for the second set of experiments. Meanwhile, in the collisions between two carom pieces case, the same thing applied, where there is a dissipated kinetic energy of 17,278% and a contact force of 1,295????10-2 N. Based on this, it can be concluded that image analysis with a long exposure technique can be used to obtain physical quantities such as speed before and after collision for collision cases in carom games. This speed data can be analyzed further to determine the amount of impulse, contact force and kinetic energy that is dissipated, where the results of the analysis show that in this collision case the conservation of energy law and momentum conservation law do not apply.